Biological variation, reference change value (RCV) and minimal important difference (MID) of inspiratory muscle strength (PImax) in patients with stable chronic heart failure - Täger, Tobias; Schell, Miriam Aline; Cebola, Rita; Fröhlich, Hanna; Dösch, Andreas; Franke, Jennifer; Katus, Hugo; Wians, Frank H.; Frankenstein, Lutz (Clinical research in cardiology, 2015)
Despite the widespread application of measurements of respiratory muscle force (PImax) in clinical trials there is no data on biological variation, reference change value (RCV), or the minimal important difference (MID) for PImax irrespective of the target cohort. We addressed this issue for patients with chronic stable heart failure.